Experiencing Organizational Change Through the Change Management Simulation: Power and Influence. (March 2020) - Lovelace, Kathi J.; Dyck, Loren R.
This resource review describes the web-based Change Management Simulation: Power and Influence by Harvard Business Publishing and discusses its application in both undergraduate and graduate courses. The simulation focuses on personal and organizational change factors that influence the adoption of a sustainability initiative within a manufacturing firm. Students experience leading strategic change in different contexts given the instructor's ability to assign different authority levels and change urgencies. We provide an overview of the simulation and suggestions for introducing, playing, and debriefing the simulation. We also briefly discuss the strengths and limitations of this supplemental pedagogy.